Atypical case of perifoveal exudative vascular anomalous complex associated with pachychoroid pigment epitheliopathy - Herda, Nabil; Semoun, Oudy; Srour, Mayer; Amoroso, Francesca; Baker, May; Capuano, Vittorio; Colantuono, Donato; Cohen, Salomon Y.; Querques, Giuseppe; Souied, Eric H. (American journal of ophthalmology case reports, 2022)
To report an unusual association of a perifoveal exudative vascular anomalous complex (PEVAC) and a bilateral pachychoroid pigment epitheliopathy (PPE), which responded positively to anti-vascular endothelial growth factor (VEGF) intravitreal injections (IVI). A 44 year-old man with no significant medical or ocular history, complained of unilateral blurred vision in his right eye (RE) over several months. On examination, best corrected visual acuity (BCVA) was 75 letters in the RE and 85 in the left eye (LE). Fundus examination in the RE showed a large perifoveal aneurysmal lesion with a macular thickening, small hemorrhages and linear hard exudates accumulation, associated with multifocal retinal pigment epithelium (RPE) changes in the posterior pole of both eyes. Optical coherence tomography of the RE showed the PEVAC as a large round retinal capillary aneurysm with surrounding intraretinal fluid, associated with serous and drusenoid RPE elevations in both eyes, consistent with PPE. Subfoveal choroidal thickness was more than 500 μm in both eyes, with several dilated choroidal veins. Fluorescein angiography showed, in the RE, the hyperfluorescent aneurysmal lesion with late leakage, associated with scattered hyperfluorescent areas in the posterior pole of both eyes. Indocyanine green angiography showed, in the RE, the same hyperfluorescent lesion but without leakage, associated with areas of choroidal hyperpermeability in both eyes. After 2 anti-VEGF IVI in the RE, good functional and anatomical improvement was observed. After 10 months of follow-up, there was no evidence of new exudation. BCVA remained stable and RPE abnormalities remained unchanged. We describe an atypical case of PEVAC associated with PPE, which responded positively to anti-VEGF therapy. To our knowledge, this is the first report of a patient presenting PEVAC and diseases of the pachychoroid spectrum. Further studies, assessing the choroid in PEVAC, are required to investigate the hypothetical relationship between these 2 entities and the efficiency of anti-VEGF therapy.